2018
DOI: 10.1038/s41598-018-34018-1
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin A inhibits Epithelial to Mesenchymal Transition in Non-Small Cell Lung Cancer Cells

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide and in the United States. Despite recent advancements in treatment approaches, metastasis remains a major therapeutic challenge in lung cancer and explains the extremely poor prognosis. Epithelial to mesenchymal transition (EMT), a complex process of cellular reprogramming has become an attractive drug target because it plays a crucial role in the metastasis of non-small cell lung cancer (NSCLC). In the present study, we examined the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…In addition, the TR-A549 cells displayed decreased E-cadherin expression, indicating an EMT phenotype which strongly suggests that EMT also plays a critical role in chemoresistance in NSCLC [43,52]. In a recent study [53], we have shown that WFA inhibits EMT in NSCLC cells, and we therefore strongly hypothesize that the use of PAC and WFA can prevent the emergence of drug resistance and metastasis in NSCLC. Together, these novel findings strongly support our rationale for combining PAC with WFA, and further suggest that this strategy has an additional benefit of the ability to prevent the emergence of drug resistance and metastasis in NSCLC.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the TR-A549 cells displayed decreased E-cadherin expression, indicating an EMT phenotype which strongly suggests that EMT also plays a critical role in chemoresistance in NSCLC [43,52]. In a recent study [53], we have shown that WFA inhibits EMT in NSCLC cells, and we therefore strongly hypothesize that the use of PAC and WFA can prevent the emergence of drug resistance and metastasis in NSCLC. Together, these novel findings strongly support our rationale for combining PAC with WFA, and further suggest that this strategy has an additional benefit of the ability to prevent the emergence of drug resistance and metastasis in NSCLC.…”
Section: Discussionmentioning
confidence: 93%
“…Withaferin A from the Solanaceae family attenuates bleomycin-induced scleroderma by targeting FoxO3a and NF-κB signaling [276]. Withaferin A (0.5 µM) can inhibit the EMT of NSCLC cells [277]. It (2 µM) can also inhibit the EMT of MCF10A cells and suppress vimentin expression in breast tumors [278].…”
Section: Reversal Of Emt By Anti-inflammatory Natural Compoundsmentioning
confidence: 99%
“…For example, studies [16,70,75] EMT phenotype in NSCLC. In a recent study [83], we have shown that WFA inhibits EMT in NSCLC cells, and we therefore strongly hypothesize that the use of PAC and WFA can prevent the emergence of drug resistance and metastasis in NSCLC. Together, these novel findings strongly support our rationale for combining PAC with WFA, and further suggest that this strategy has an additional benefit of the ability to prevent the emergence or target drug resistance and metastasis in NSCLC.…”
Section: Wfa Targets Pac Resistant Tra549 Nsclc Cells In Vitro and Inmentioning
confidence: 89%
“…Chemically, WFA is a plant-derived steroidal-lactone that was first isolated from the alcoholic extracts of the Ayurvedic medicinal plant Withania somnifera [23,24,26]. In literature, there is a growing body of in vitro and in vivo preclinical data to demonstrable the efficacy of WFA against NSCLC [62,83], breast [31,35], cervical [66], prostate [39,94], pancreatic [67], renal [116], B-cell lymphoma [68] and ovarian cancers [43].…”
Section: Repeated Dosing Toxicity and Pharmacokinetics Of Withaferin mentioning
confidence: 99%
See 1 more Smart Citation